Case studies in marketing management - Gupta, S. L. (Pentagon Press, 2007)
Marketing is a dynamic field and the marketing profession has to be innovative to understand the pulse of consumers and develop strategies to serve them better. Marketing fundamentals need to be sharpened on continuous basis using case studies, role plays, simulation, and projects. This book presents case studies in modern marketing management.